Antibodies to hepatitis B surface antigen prevent viral reactivation in recipients of liver grafts from anti-HBC positive donors. Issue 1 (1st January 2002) - Roque-Afonso, A M; Feray, C; Samuel, D; Simoneau, D; Roche, B; Emile, J-F; Gigou, M; Shouval, D; Dussaix, E
Abstract : Background and aims: Liver donors with serological evidence of resolved hepatitis B virus (HBV) infection (HBV surface antigen (HBsAg) negative, anti-HBV core (HBc) positive) can transmit HBV infection to recipients. In the context of organ shortage, we investigated the efficacy of hepatitis B immunoglobulin (HBIG) to prevent HBV infection, and assessed the infectious risk by polymerase chain reaction (PCR) testing for HBV DNA on serum and liver tissue of anti-HBc positive donors. Patients: Between 1997 and 2000, 22 of 315 patients were transplanted with liver allografts from anti-HBc positive donors. Long term HBIG therapy was administered to 16 recipients. Four naive and two vaccinated patients received no prophylaxis. Results: Hepatitis B developed in the four HBV naive recipients without prophylaxis and in none of the vaccinated subjects. Among the 16 recipients receiving HBIG, one patient with residual anti-HBs titres below 50 UI/ml became HBsAg positive. The remaining 15 remained HBsAg negative and HBV DNA negative by PCR testing throughout a 20 month (range 4–39) follow up period. HBV DNA was detected by PCR in 1/22 donor serum, and in 11/21 liver grafts with normal histology. A mean of 12 months post-transplantation (range 1–23) HBV DNA was no longer detectable in graft biopsies from patients remaining HBsAg negative. Conclusion: Anti-HBs antibodies may control HBV replication in liver grafts from anti-HBc positive donors, without additional antiviral drugs. These grafts are thus suitable either to effectively vaccinated recipients or to those who are given HBIG to prevent HBV recurrence.